A highly sensitive and selective hypochlorite fluorescent probe based on oxidation of hydrazine via free radical mechanism. (March 2016) - Cheng, Tanyu; Zhao, Junwei; Wang, Ziyun; An, Juzeng; Xu, Yufang; Qian, Xuhong; Liu, Guohua
Abstract: Developing fluorescent probes for selective and sensitive detection of hypochlorite has received much attention, because hypochlorite is closely related to human health. In this work, a new fluorescent probe based on dipyrromethene boron difluoride (BODIPY) fluorophore using hydrazine as detecting group for hypochlorite was synthesized and fully characterized. The reaction of the probe with sodium hypochlorite is complete within 1 min in phosphate-buffered saline, and the fluorescence of the system significantly enhanced. The probe also exhibits admirable sensitivity and selectivity as well. The results of nuclear magnetic resonance monitoring and high-performance liquid chromatography analysis indicate that the detection process plausibly involves a free radical oxidation mechanism. Graphical abstract: Highlights: A BODIPY-based probe is developed for detection of hypochlorite. This probe displays excellent reactivity with sodium hypochlorite. This probe exhibits high sensitivity and selectivity in PBS buffer solution.